THE EFFECT OF DIVERSITY MANAGEMENT IN THE CONTEXT OF HUMAN RESOURCES ON TALENT MANAGEMENT - Ben Matug, Mohamed Ali; Demirel, Yavuz (EUropean Journal of Managerial Research (EUJMR), 2024)
In a globalized world, organizations with multicultural environments are increasingly common and the need for diverse types of talents and skills is becoming necessary. Diversity imposes many advantages and opportunities for the organization; however, there are other challenges that accompany the phenomenon. The study targets investigating the effect of diversity management and its dimensions on talent management using statistical evidence and through the case study of A total of 430 valid questionnaires were collected from subjects in Turkey and Libya. The two concepts are two important mechanisms used in organizations around the world to identify potential talents, develop them, and use it individual and collective powers to increase the efficiency and competency of the organization. The investigation of the influence of diversity management on talent management is necessary to understand the success and failure factors in organizations with diversified culture and operations. Diversity management is a human resource practice that is meant to turn diversity in gender, culture, and talent into an empowerment tool. The comprehension of the effect of diversity management on talent management allows professionals to focus on specific diversity management components that can enhance talent management practices.